State of the Art and Future Trends in Material Modeling - Altenbach, Holm.; Öchsner, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This special anniversary book celebrates the success of this Springer book series highlighting materials modeling as the key to developing new engineering products and applications. In this 100th volume of "Advanced Structured Materials", international experts showcase the current state of the art and future trends in materials modeling, which is essential in order to fulfill the demanding requirements of next-generation engineering tasks. .
1 On Viscoelasticity in the Theory of Geometrically Linear Plates -- 2 Teaching Mechanics -- 3 Modeling of Damage of Ductile Materials -- 4 Creep in Heat-resistant Steels at Elevated Temperatures. .
Keywords: Materials -- Analysis; Mechanics, Applied; Solids; Mechanics; Characterization and Analytical Technique; Solid Mechanics; Classical Mechanics